A PCT resin composition and its preparation method and application

By feeding PCT resin premix and reinforcement respectively in the twin screw extruder, PCT resin compositions with high reflectivity, excellent mechanical properties and good hydrolysis and aging properties are prepared, which solves the problem that PCT resin cannot meet the needs of high-quality products when used as an LED packaging material in the prior art, and achieves significant performance improvement and cost control.

CN119350821BActive Publication Date: 2025-03-25DAWN POLYMER MATERIALS (CHONGQING) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411918352.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-25
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

In the prior art, when PCT resin is used as an LED packaging material, it cannot meet the needs of high-quality products, and the improvement costs are high, making it difficult to achieve popular production.

Method used

By feeding the PCT resin premix and reinforcement into the main feeding system and side feeding system of the twin-screw extruder respectively, and making it by melt extrusion, PCT resin compositions with high reflectivity, excellent tensile strength and bending strength, and good performance after hydrolysis and aging were prepared.

Benefits of technology

The reflectivity of the PCT resin composition reaches 98.42-98.87%, the tensile strength is 48.54-49.25Mpa, the bending strength is 89.42-90.01Mpa, and the tensile strength retention rate after hydrolysis and aging is 94.80-95.52%, meeting the high-quality product demand in the field of LED packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

The present invention relates to the technical field of polymer composite materials, and in particular to a PCT resin composition and a preparation method and application thereof. The PCT resin composition is prepared by feeding a PCT resin premix and a reinforcing agent in a mass ratio of (57.9-123):(5-20) into a main feeding system and a side feeding system of a twin-screw extruder respectively and then being melt-extruded. The present invention obtains a PCT resin composition with excellent performance through a specific formula and a proportion and combination corresponding to the formula, and through a specific preparation process. The excellent performance enables the PCT resin composition prepared by the present invention to meet the relevant requirements for preparing high-end packaging materials as a raw material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer composite materials, and in particular to a PCT resin composition and a preparation method and application thereof. Background Art

[0002] LED is a semiconductor light-emitting diode, a semiconductor device that can convert electrical energy into light energy. LED packaging materials need to have characteristics such as high temperature resistance, UV resistance and low water absorption. Author Zhang Lei et al. mentioned the current research progress of polymer-based LED packaging bracket matrix resin in the journal "Engineering Plastics Application" Volume 49, Issue 1, titled "Research Progress of High-Power LED Packaging Bracket Matrix Resin", and disclosed the characteristics of new packaging bracket matrix resins such as general polyphthalic acid polyamide resin (PPA), polycyclohexane dimethyl terephthalate (PCT), aromatic thermotropic liquid crystal polyester resin (LCP), epoxy resin (EMC), silicone modified molding compound (SMC) and unsaturated polyester resin (UP). The material properties of the resins such as initial reflectivity, aging reflectivity, heat resistance temperature, glass transition temperature and water absorption were compared, and the comparative advantages and limitations of different resins in practical applications were emphasized.

[0003] Polycyclohexylene dimethylene terephthalate resin (PCT resin), as a high temperature resistant, semi-crystalline thermoplastic, is polymerized from 1,4-cyclohexanedimethanol (CHDM) and dimethyl terephthalate (DMT). PCT resin has excellent toughness, thermal stability, easy processing, chemical corrosion resistance and low hygroscopicity, which enables it to maintain stable mechanical properties and processing properties in a humid environment. However, the heat resistance, hydrolysis stability and anti-yellowing properties of PCT resin cannot meet the use requirements of high-quality products in the field of LED packaging. Therefore, the preparation of PCT resin materials has been studied in the prior art.

[0004] For example, CN118530563A discloses a polyester composition, which includes the following components by weight: 64-66 parts of PCT resin; 20-40 parts of white pigment; 5-25 parts of reinforcing filler; 0.1-1.2 parts of cage-shaped polysilsesquioxane; 0-2 parts of auxiliary agent. The polyester composition obtained by this technical solution has an initial light reflectivity of ≥90%, a thermal oxygen aging bending strength retention rate of ≥82%, a hydrolysis test tensile strength retention rate of ≥83%, and a glue bonding strength of ≥23MPa. Although the performance in various aspects has been improved, it still cannot meet the use requirements of high-quality products in the field of LED packaging, such as a reflectivity of more than 95% or a tensile strength retention rate of more than 90% after hydrolysis aging.

[0005] CN118271800A discloses a liquid crystal fiber reinforced polyester resin composition and its preparation method and application. The liquid crystal fiber reinforced polyester resin composition comprises the following components calculated by weight: 100 parts of PCT resin; 5-50 parts of white pigment; 5-30 parts of liquid crystal fiber; 0.5-5 parts of auxiliary agent; wherein the fineness of the liquid crystal fiber is 900-3200D. The PCT resin, white pigment, auxiliary agent and liquid crystal fiber are mixed evenly, and then melt blended and extruded and granulated by a twin-screw extruder to obtain a liquid crystal fiber reinforced polyester resin composition. However, the main raw material of liquid crystal fiber is liquid crystal polymer. The synthesis of this type of polymer is relatively complex, and usually requires the use of some special monomers and solvents, which is costly. Moreover, high-quality liquid crystal polymers often rely on imports or require high R&D investment to produce, making it difficult to reduce the cost of raw materials.

[0006] Based on the above-mentioned existing technologies, there are technical problems in the existing technologies that need to be solved urgently, such as the inability of PCT resin as an LED packaging material to meet the performance requirements of high-quality packaging materials, the cost is greatly increased after improvement, and it is difficult to carry out popular production. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a PCT resin composition, wherein the PCT resin composition is prepared by feeding a PCT resin premix and a reinforcing agent in a mass ratio of (57.9-123):(5-20) into a main feeding system and a side feeding system of a twin-screw extruder respectively and then being melt-extruded;

[0008] The PCT resin premix is ​​made of polycyclohexylene dimethylene terephthalate resin (PCT resin), a modified brightener, a toughening agent, a nucleating agent, a lubricant, a light stabilizer, an antioxidant, and an anti-hydrolysis agent;

[0009] In parts by weight, the components and contents in the PCT resin premix are as follows:

[0010] Polycyclohexylene dimethylene terephthalate resin (PCT resin): 45.0-60.0 parts by weight;

[0011] Modified brightener: 10.2-41.0 parts by weight;

[0012] Toughening agent: 1.0-8.0 parts by weight;

[0013] Nucleating agent: 0.1-2.0 parts by weight;

[0014] Lubricant: 0.5-3.0 parts by weight;

[0015] Light stabilizer: 0.5-3.0 parts by weight;

[0016] Antioxidant: 0.5-3.0 parts by weight;

[0017] Anti-hydrolysis agent: 0.1-3.0 parts by weight;

[0018] The modified brightener is prepared by heating and modifying a brightener and a coupling agent; the mass ratio of the brightener and the coupling agent is (10-40): (0.2-1);

[0019] The PCT resin composition has a reflectivity of 98.42-98.87%, a tensile strength of 48.54-49.25 MPa, a flexural strength of 89.42-90.01 MPa, and an impact strength of 3.05-3.65 kJ / m 2 , the tensile strength retention rate after hydrolysis aging is 94.80-95.52%, the heat deformation temperature is 193.4-195.6℃, the color value before aging is 97.57-98.42, the color value after aging is 93.45-94.13, and the color value difference before and after aging is 3.82-4.94;

[0020] The color value is the L value.

[0021] Further, the reflectivity is measured according to the CIE Lab color difference evaluation standard, using a Minolta3600D spectrophotometer at a wavelength of 460 nm as the initial reflectivity;

[0022] The tensile strength is the data obtained by tensile testing at room temperature according to ISO-527 standard, and the tensile test rate is 50 mm / min;

[0023] The bending strength is the data obtained by bending strength test at room temperature according to ISO-178 standard, and the bending test rate is 2mm / min;

[0024] The impact strength is the data obtained by performing an Izod impact test at room temperature according to ISO-179-1 standard;

[0025] The tensile strength after hydrolysis aging is obtained by placing the test specimen in a pressure cooker and boiling it for 24 hours according to ISO-527 standard, and then performing a tensile test at room temperature. The tensile test rate is 50 mm / min. Specifically, the tensile strength retention rate after hydrolysis aging is equal to the tensile strength after aging divided by the tensile strength before aging;

[0026] The heat deformation temperature is the data obtained by testing at room temperature according to ISO-75-2 standard, with a heating rate of 120°C / h;

[0027] The aging color value test conditions are as follows: the aging temperature is 180° C., the aging time is 72 h, and the test is performed using a colorimeter.

[0028] Furthermore, the reinforcing agent is round glass fiber with a fiber diameter of ≤10 μm.

[0029] Furthermore, the polycyclohexylene dimethylene terephthalate resin (PCT resin) has a melt index of 20-50 g / 10 min at a temperature of 300° C. and a load of 1.2 kg.

[0030] Furthermore, the polycyclohexylene dimethylene terephthalate resin (PCT resin) is in powder form.

[0031] Furthermore, the toughening agent is one of ethylene-butyl acrylate-glycidyl methacrylate copolymer (EBA-GMA), methyl methacrylate-butadiene-styrene copolymer (MBS), and polyolefin elastomer (POE).

[0032] Furthermore, the nucleating agent is one of N-butylpyrazone methyl salt and montanic acid sodium salt.

[0033] Furthermore, the lubricant is one of ethylene acrylic acid copolymer (EAA), silicone masterbatch, and oxidized polyethylene wax.

[0034] Furthermore, the light stabilizer is a methylamide light stabilizer.

[0035] Furthermore, the molecular structure of the methylamide light stabilizer is:

[0036] .

[0037] Furthermore, the antioxidant is at least two of a phosphite antioxidant, a benzofuranone antioxidant, and an acrylate antioxidant.

[0038] Furthermore, the molecular structure of the phosphite antioxidant is:

[0039] .

[0040] Furthermore, the molecular structure of the benzofuranone antioxidant is:

[0041] .

[0042] Furthermore, the molecular structure of the acrylate antioxidant is:

[0043] .

[0044] Furthermore, the anti-hydrolysis agent is polycarbodiimide.

[0045] Furthermore, the whitening agent is silicon-aluminum coated nano titanium dioxide.

[0046] Furthermore, the silicon-aluminum coated nano titanium dioxide is a core-shell structure, with nano titanium dioxide as the core and silicon-aluminum oxide as the coating layer, and the thickness of the coating layer is 4-50nm;

[0047] The core-shell structure can effectively isolate the nano-titanium dioxide from the external environment and protect the core nano-titanium dioxide particles;

[0048] The silicon compound is bonded to the TiO2 surface through the Ti-O-Si bond, and the aluminum oxide exists in the form of boehmite (γ-AlOOH, also known as hydrated alumina) and / or amorphous Al (OH)3, and chemically bonds with active groups such as hydroxyl groups on the surface of nano-titanium dioxide, thereby enhancing the bonding force between the coating and the core and improving the stability of the coating.

[0049] Furthermore, the coupling agent is one of a titanate coupling agent, an aluminate coupling agent, an aluminozirconate coupling agent, and a silane coupling agent.

[0050] The present invention also provides a method for preparing the PCT resin composition, comprising the following steps:

[0051] Step 1, drying the polycyclohexylene dimethylene terephthalate resin (PCT resin) for a first time and setting it aside; drying the brightener for a second time and setting it aside; and drying the enhancer for a third time and setting it aside;

[0052] Step 2, adding the coupling agent into the brightener dried in step 1, and stirring at high speed to obtain a modified brightener;

[0053] Step 3, the polycyclohexylene dimethylene terephthalate resin in step 1, the modified brightener, toughening agent, nucleating agent, lubricant, light stabilizer, antioxidant, and anti-hydrolysis agent in step 2 are mixed at a high speed according to a proportion to obtain a PCT resin premix;

[0054] Step 4: Feed the PCT resin premix of step 3 and the reinforcing agent dried in step 1 into the main feeding system and the side feeding system of the twin-screw extruder respectively and obtain the PCT resin composition by melt extrusion granulation.

[0055] Furthermore, in step 1, the temperature of the first drying is 100-110° C. and the time is 5-8 hours;

[0056] The second drying temperature is 80-90°C and the time is 4-5h;

[0057] The temperature of the third drying is 80-90° C. and the time is 3-4 hours.

[0058] Furthermore, in step 1, a high-speed powder mill is used to grind the dried PCT resin into powder, which is beneficial for mixing and dispersing with other raw materials.

[0059] Furthermore, the high-speed stirring rate in step 2 is 500-1000 rad / min, and the time is 5-8 min. During the high-speed stirring process, the coupling agent reacts with the hydroxyl group or oxide included in the brightener to form corresponding chemical bonds, thereby achieving modification of the brightener.

[0060] Furthermore, the modified brightener is left standing for no more than 24 hours to prevent it from combining with moisture in the air again and affecting subsequent processes.

[0061] Furthermore, the high-speed mixing rate in step 3 is 500-1000 rad / min, and the time is 3-5 min.

[0062] Furthermore, in step 4, the main feeding system is connected to the first zone of the twin-screw extruder, and the side feeding system is connected to the fourth zone of the twin-screw extruder.

[0063] Furthermore, in step 4, inert gas is introduced into the main feeding system and the side feeding system during the extrusion process.

[0064] Furthermore, the inert gas includes but is not limited to one or more of nitrogen and argon.

[0065] Further, the twin-screw extruder described in step 4 includes ten temperature zones, and the temperatures of each zone are set to 260-280°C in zone 1, 260-280°C in zone 2, 260-280°C in zone 3, 240-280°C in zone 4, 240-280°C in zone 5, 240-280°C in zone 6, 260-280°C in zone 7, 260-280°C in zone 8, 260-280°C in zone 9, and 260-280°C in zone 10.

[0066] Furthermore, the aspect ratio of the twin-screw extruder in step 4 is 40:1, the screw speed is 200-400r / min, the feeding speed of the main feeding system is 10-50Hz, and the feeding speed of the side feeding system is 4.5-7Hz.

[0067] Furthermore, in step 4, a granulator is used for granulation.

[0068] The present invention also provides a packaging material, which is prepared from the PCT resin composition.

[0069] The beneficial effects of the present invention are:

[0070] 1. The present invention provides a PCT resin composition, wherein the PCT resin composition is prepared by feeding a PCT resin premix and a reinforcing agent in a mass ratio of (57.9-123): (5-20) into a main feeding system and a side feeding system of a twin-screw extruder respectively and then melt-extruding; the present invention obtains a PCT resin composition having a reflectivity of 98.42-98.87%, a tensile strength of 48.54-49.25 Mpa, a flexural strength of 89.42-90.01 Mpa, and an impact strength of 3.05-3.65 kJ / m through a specific formula and a corresponding ratio and combination of the formulas and a specific preparation process. 2 , the tensile strength retention rate after hydrolysis aging is 94.80-95.52%, the heat deformation temperature is 193.4-195.6°C, the color value (L value) before aging is 97.57-98.42, the color value (L value) after aging is 93.45-94.13, and the color value (L value) difference before and after aging is 3.82-4.94 PCT resin composition; and these excellent properties enable the PCT resin composition prepared by the present invention to meet the relevant requirements for preparing high-end packaging materials as raw materials;

[0071] 2. The reinforcing agent selected in the preparation of the PCT resin composition of the present invention is round glass fiber with a fiber diameter of ≤10 μm, wherein the round glass fiber has good fluidity in the preparation of the PCT resin composition due to its special round structure, can be evenly distributed with the flow of the resin during the preparation process, and is not prone to fiber agglomeration or uneven orientation, which is helpful for preparing a PCT resin composition with uniform structure and stable performance, and improving production efficiency and product quality;

[0072] 3. The antioxidant selected when preparing the PCT resin composition of the present invention is a compound of at least two of phosphite antioxidants, benzofuranone antioxidants, and acrylate antioxidants. A single antioxidant will not only reduce the anti-oxidation or color value of the PCT resin composition, but also reduce other properties, such as reflectivity, tensile strength, flexural strength, impact strength, heat deformation temperature, etc. It can be seen that at least two antioxidants must be used in the preparation process of the present invention, and the two antioxidants not only have a synergistic enhancement effect to form a complete antioxidant defense system, but also have a certain auxiliary enhancement effect in the preparation with other raw materials, so that the performance of the PCT resin composition prepared by the present invention is improved;

[0073] 4. Before the preparation, the polycyclohexylene dimethylene terephthalate resin (PCT resin), brightener, and enhancer are dried under specific drying conditions to remove moisture and / or volatiles contained therein, to prevent oxidation or decomposition thereof in the subsequent preparation process, and to improve the quality and stability of the PCT resin composition. The dried PCT resin is powdered using a high-speed powdering machine, which is beneficial for mixing and dispersing with other raw materials.

[0074] 5. In the process of extrusion by the twin-screw extruder of the present invention, an inert gas is selected for protection. In addition to ensuring the yellowing resistance of the PCT resin composition and improving the color value, the other properties are also improved. It can be seen that during the preparation process, the introduction of inert gas can eliminate the interference of external air or impurities in the entire extrusion process, greatly improving the performance of the PCT resin composition. DETAILED DESCRIPTION

[0075] Example 1

[0076] This embodiment provides a PCT resin composition, wherein the PCT resin composition is prepared by feeding a PCT resin premix and a reinforcing agent round glass fiber in a mass ratio of 85.7:5 into a main feeding system and a side feeding system of a twin-screw extruder respectively and then being melt-extruded;

[0077] The PCT resin premix is ​​made of 51 parts by weight of PCT resin, 30.2 parts by weight of modified whitening agent, 2 parts by weight of toughening agent ethylene-butyl acrylate-glycidyl methacrylate copolymer (EBA-GMA), 0.5 parts by weight of nucleating agent sodium montanate, 0.5 parts by weight of lubricant ethylene acrylic acid copolymer (EAA), 0.7 parts by weight of light stabilizer methyl amide light stabilizer, 0.2 parts by weight of phosphite antioxidant and 0.4 parts by weight of benzofuranone antioxidant, and 0.2 parts by weight of anti-hydrolysis agent polycarbodiimide;

[0078] The modified brightener is prepared by heating and modifying the brightener silicon-aluminum coated nano titanium dioxide and the silane coupling agent in a mass ratio of 30:0.2;

[0079] The PCT resin composition has a reflectivity of 98.87%, a tensile strength of 49.25 MPa, a flexural strength of 89.42 MPa, and an impact strength of 3.65 kJ / m 2 The hydrolysis aging tensile strength retention rate is 95.52%, the heat deformation temperature is 195.6℃, the color value (L value) before aging is 98.33, the color value (L value) after aging is 94.13, and the color value (L value) difference before and after aging is 4.20.

[0080] The reinforcing agent is round glass fiber with a fiber diameter of ≤10 μm.

[0081] The PCT resin has a melt index of 20 g / 10 min at a temperature of 300° C. and a load of 1.2 kg;

[0082] This embodiment also provides a method for preparing a PCT resin composition, comprising the following steps:

[0083] Step 1, drying poly(cyclohexylene dimethylene terephthalate) resin (PCT resin) for standby use; the first drying temperature is 100° C., the time is 8 hours, and the dried PCT resin is powdered using a high-speed powdering machine;

[0084] The brightener is dried for the second time and then used for later use; the temperature of the second drying is 80°C and the time is 5h;

[0085] The enhancer is dried for the third time and then used for later use; the temperature of the third drying is 80°C and the time is 4h;

[0086] Step 2, putting the coupling agent into the brightener dried in step 1, and stirring at high speed to obtain a modified brightener; the high-speed stirring rate is 500 rad / min, and the time is 8 minutes, so that the coupling agent reacts with the hydroxyl group or oxide included in the brightener to form a corresponding chemical bond, thereby modifying the brightener and improving the dispersibility and stability of the brightener; wherein the modified brightener is placed for no more than 24 hours to prevent it from combining with moisture in the air again and affecting subsequent processes;

[0087] Step 3, the polycyclohexylene dimethylene terephthalate resin powdered in step 1, the modified brightener, toughening agent, nucleating agent, lubricant, light stabilizer, antioxidant, and anti-hydrolysis agent in step 2 are mixed at a high speed according to a proportion at a rate of 1000 rad / min for 3 minutes to obtain a PCT resin premix;

[0088] Step 4, feeding the PCT resin premix of step 3 and the reinforcing agent dried in step 1 into the main feeding system and the side feeding system of the twin-screw extruder respectively and extrude them by melt, and introducing nitrogen into the main feeding system and the side feeding system respectively during the extrusion process, and finally obtaining a PCT resin composition by extrusion and granulation using a granulator;

[0089] The main feeding system is in communication with a zone one of the twin-screw extruder, and the side feeding system is in communication with a zone four of the twin-screw extruder;

[0090] The twin-screw extruder includes ten temperature zones, and the temperatures of the zones are set to 260°C for zone 1, 265°C for zone 2, 265°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 270°C for zone 7, 280°C for zone 8, 280°C for zone 9, and 280°C for zone 10;

[0091] The length-to-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 200 r / min, the feeding speed of the main feeding system is 25.5 Hz, and the feeding speed of the side feeding system is 4.5 Hz.

[0092] Example 2

[0093] This embodiment provides a PCT resin composition, wherein the PCT resin composition is prepared by feeding a PCT resin premix and a reinforcing agent round glass fiber in a mass ratio of 85.1:17 into a main feeding system and a side feeding system of a twin-screw extruder respectively and then being melt-extruded;

[0094] The PCT resin premix is ​​made of 50.7 parts by weight of PCT resin, 28.3 parts by weight of modified whitening agent, 2 parts by weight of toughening agent polyolefin elastomer (POE), 0.2 parts by weight of nucleating agent N-butylpyracloic acid methyl salt, 2 parts by weight of lubricant silicone masterbatch, 0.5 parts by weight of light stabilizer methylamide light stabilizer, 0.2 parts by weight of phosphite antioxidant, 0.4 parts by weight of benzofuranone antioxidant, 0.4 parts by weight of acrylate antioxidant, and 0.4 parts by weight of anti-hydrolysis agent polycarbodiimide;

[0095] The modified whitening agent is prepared by heating and modifying the whitening agent silicon-aluminum coated nano titanium dioxide and titanate coupling agent in a mass ratio of 28:0.3;

[0096] The PCT resin composition has a reflectivity of 98.42%, a tensile strength of 48.54 MPa, a flexural strength of 90.01 MPa, and an impact strength of 3.34 kJ / m 2 The hydrolysis aging tensile strength retention rate is 94.80%, the heat deformation temperature is 194.4℃, the color value (L value) before aging is 97.57, the color value (L value) after aging is 93.45, and the color value (L value) difference before and after aging is 4.12.

[0097] The reinforcing agent is round glass fiber with a fiber diameter of ≤10 μm.

[0098] The PCT resin has a melt index of 30 g / 10 min at a temperature of 300° C. and a load of 1.2 kg;

[0099] This embodiment also provides a method for preparing a PCT resin composition, comprising the following steps:

[0100] Step 1, drying poly(cyclohexylene dimethylene terephthalate) resin (PCT resin) for standby use; the first drying temperature is 110° C., the time is 5 hours, and the dried PCT resin is powdered using a high-speed powder grinder;

[0101] The brightener is dried for the second time and then used for later use; the temperature of the second drying is 90°C and the time is 4 hours;

[0102] The enhancer is dried for the third time and then used for later use; the temperature of the third drying is 90°C and the time is 3h;

[0103] Step 2, putting the coupling agent into the brightener dried in step 1, and stirring at high speed to obtain a modified brightener; the high-speed stirring rate is 1000 rad / min, and the time is 5 minutes, so that the coupling agent reacts with the hydroxyl group or oxide included in the brightener to form a corresponding chemical bond, thereby modifying the brightener and improving the dispersibility and stability of the brightener; wherein the modified brightener is placed for no more than 24 hours to prevent it from combining with moisture in the air again and affecting subsequent processes;

[0104] Step 3, the polycyclohexylene dimethylene terephthalate resin powdered in step 1, the modified brightener, toughening agent, nucleating agent, lubricant, light stabilizer, antioxidant, and anti-hydrolysis agent in step 2 are mixed at a high speed according to a proportion at a rate of 500 rad / min for 5 minutes to obtain a PCT resin premix;

[0105] Step 4, feeding the PCT resin premix of step 3 and the reinforcing agent dried in step 1 into the main feeding system and the side feeding system of the twin-screw extruder respectively and extrude them by melt, and introducing nitrogen into the main feeding system and the side feeding system respectively during the extrusion process, and finally obtaining a PCT resin composition by extrusion and granulation using a granulator;

[0106] The main feeding system is in communication with a zone one of the twin-screw extruder, and the side feeding system is in communication with a zone four of the twin-screw extruder;

[0107] The twin-screw extruder includes ten temperature zones, and the temperatures of the zones are respectively set at 280°C for zone 1, 260°C for zone 2, 260°C for zone 3, 280°C for zone 4, 240°C for zone 5, 240°C for zone 6, 260°C for zone 7, 260°C for zone 8, 280°C for zone 9, and 280°C for zone 10;

[0108] The length-to-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 300 r / min, the feeding speed of the main feeding system is 10 Hz, and the feeding speed of the side feeding system is 7 Hz.

[0109] Example 3

[0110] This embodiment provides a PCT resin composition, wherein the PCT resin composition is prepared by feeding a PCT resin premix and a reinforcing agent round glass fiber in a mass ratio of 60.5:20 into a main feeding system and a side feeding system of a twin-screw extruder respectively and then being melt-extruded;

[0111] The PCT resin premix is ​​made of 45 parts by weight of PCT resin, 10.8 parts by weight of modified whitening agent, 1 part by weight of toughening agent methyl methacrylate-butadiene-styrene copolymer (MBS), 0.1 parts by weight of nucleating agent sodium montanate, 1 part by weight of lubricant oxidized polyethylene wax, 2 parts by weight of light stabilizer methyl amide light stabilizer, 0.3 parts by weight of benzofuranone antioxidant and 0.2 parts by weight of acrylate antioxidant, and 0.1 parts by weight of anti-hydrolysis agent polycarbodiimide;

[0112] The modified brightener is prepared by heating and modifying the brightener silicon-aluminum coated nano titanium dioxide and aluminate coupling agent in a mass ratio of 10:0.8;

[0113] The PCT resin composition has a reflectivity of 98.53%, a tensile strength of 49.12 MPa, a flexural strength of 89.44 MPa, and an impact strength of 3.05 kJ / m 2 The hydrolysis aging tensile strength retention rate is 95.09%, the heat deformation temperature is 194.1℃, the color value (L value) before aging is 98.42, the color value (L value) after aging is 93.48, and the color value (L value) difference before and after aging is 4.94.

[0114] The reinforcing agent is round glass fiber with a fiber diameter of ≤10 μm.

[0115] The PCT resin has a melt index of 40 g / 10 min at a temperature of 300° C. and a load of 1.2 kg;

[0116] This embodiment also provides a method for preparing a PCT resin composition, comprising the following steps:

[0117] Step 1, drying poly(cyclohexylene dimethylene terephthalate) resin (PCT resin) for standby use; the first drying temperature is 110° C., the time is 5 hours, and the dried PCT resin is powdered using a high-speed powder grinder;

[0118] The brightener is dried for the second time and then used for later use; the temperature of the second drying is 90°C and the time is 5h;

[0119] The enhancer is dried for the third time and then used for later use; the temperature of the third drying is 80°C and the time is 3h;

[0120] Step 2, putting the coupling agent into the brightener dried in step 1, and stirring at high speed to obtain a modified brightener; the high-speed stirring rate is 800 rad / min, and the time is 6 minutes, so that the coupling agent reacts with the hydroxyl group or oxide included in the brightener to form a corresponding chemical bond, thereby modifying the brightener and improving the dispersibility and stability of the brightener; wherein the modified brightener is placed for no more than 24 hours to prevent it from combining with moisture in the air again and affecting subsequent processes;

[0121] Step 3, the polycyclohexylene dimethylene terephthalate resin powdered in step 1, the modified brightener, toughening agent, nucleating agent, lubricant, light stabilizer, antioxidant, and anti-hydrolysis agent in step 2 are mixed at a high speed according to a proportion at a rate of 700 rad / min for 4 minutes to obtain a PCT resin premix;

[0122] Step 4, feeding the PCT resin premix of step 3 and the reinforcing agent dried in step 1 into the main feeding system and the side feeding system of the twin-screw extruder respectively and extrude them by melt, and introducing nitrogen into the main feeding system and the side feeding system respectively during the extrusion process, and finally obtaining a PCT resin composition by extrusion and granulation using a granulator;

[0123] The main feeding system is in communication with a zone one of the twin-screw extruder, and the side feeding system is in communication with a zone four of the twin-screw extruder;

[0124] The twin-screw extruder includes ten temperature zones, and the temperatures of the zones are set to 260°C for zone 1, 280°C for zone 2, 280°C for zone 3, 240°C for zone 4, 240°C for zone 5, 240°C for zone 6, 280°C for zone 7, 260°C for zone 8, 260°C for zone 9, and 260°C for zone 10;

[0125] The length-to-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 400 r / min, the feeding speed of the main feeding system is 40 Hz, and the feeding speed of the side feeding system is 5.5 Hz.

[0126] Example 4

[0127] This embodiment provides a PCT resin composition, wherein the PCT resin composition is prepared by feeding a PCT resin premix and a reinforcing agent round glass fiber in a mass ratio of 123:10 into a main feeding system and a side feeding system of a twin-screw extruder respectively and then being melt-extruded;

[0128] The PCT resin premix is ​​made of 60 parts by weight of PCT resin, 41 parts by weight of modified brightener, 8 parts by weight of toughening agent methyl methacrylate-butadiene-styrene copolymer (MBS), 2 parts by weight of nucleating agent N-butylpyracloic acid methyl salt, 3 parts by weight of lubricant oxidized polyethylene wax, 3 parts by weight of light stabilizer methyl amide light stabilizer, 1 part by weight of benzofuranone antioxidant and 2 parts by weight of acrylate antioxidant, and 3 parts by weight of anti-hydrolysis agent polycarbodiimide;

[0129] The modified brightener is prepared by heating and modifying the brightener silicon-aluminum coated nano titanium dioxide and aluminum zirconate coupling agent in a mass ratio of 40:1;

[0130] The PCT resin composition has a reflectivity of 98.61%, a tensile strength of 48.97 MPa, a flexural strength of 89.65 MPa, and an impact strength of 3.34 kJ / m 2 The hydrolysis aging tensile strength retention rate is 95.28%, the heat deformation temperature is 193.4℃, the color value (L value) before aging is 97.92, the color value (L value) after aging is 94.10, and the color value (L value) difference before and after aging is 3.82.

[0131] The reinforcing agent is round glass fiber with a fiber diameter of ≤10 μm.

[0132] The PCT resin has a melt index of 50 g / 10 min at a temperature of 300° C. and a load of 1.2 kg;

[0133] This embodiment also provides a method for preparing a PCT resin composition, comprising the following steps:

[0134] Step 1, drying poly(cyclohexylene dimethylene terephthalate) resin (PCT resin) for standby use; the first drying temperature is 100° C., the time is 7 hours, and the dried PCT resin is powdered using a high-speed powdering machine;

[0135] The brightener is dried for the second time and then used for later use; the temperature of the second drying is 90°C and the time is 4 hours;

[0136] The enhancer is dried for the third time and then used for later use; the temperature of the third drying is 80°C and the time is 4h;

[0137] Step 2, putting the coupling agent into the brightener dried in step 1, and stirring at high speed to obtain a modified brightener; the high-speed stirring rate is 800 rad / min, and the time is 7 minutes, so that the coupling agent reacts with the hydroxyl group or oxide included in the brightener to form a corresponding chemical bond, thereby modifying the brightener and improving the dispersibility and stability of the brightener; wherein the modified brightener is placed for no more than 24 hours to prevent it from combining with moisture in the air again and affecting subsequent processes;

[0138] Step 3, the polycyclohexylene dimethylene terephthalate resin powdered in step 1, the modified brightener, toughening agent, nucleating agent, lubricant, light stabilizer, antioxidant, and anti-hydrolysis agent in step 2 are mixed at a high speed according to a proportion at a rate of 800 rad / min for 4 minutes to obtain a PCT resin premix;

[0139] Step 4, feeding the PCT resin premix of step 3 and the reinforcing agent dried in step 1 into the main feeding system and the side feeding system of the twin-screw extruder respectively and extrude them by melt, and introducing nitrogen into the main feeding system and the side feeding system respectively during the extrusion process, and finally obtaining a PCT resin composition by extrusion and granulation using a granulator;

[0140] The main feeding system is in communication with a zone one of the twin-screw extruder, and the side feeding system is in communication with a zone four of the twin-screw extruder;

[0141] The twin-screw extruder includes ten temperature zones, and the temperatures of the zones are set to 260°C for zone 1, 280°C for zone 2, 280°C for zone 3, 240°C for zone 4, 280°C for zone 5, 280°C for zone 6, 280°C for zone 7, 260°C for zone 8, 260°C for zone 9, and 270°C for zone 10;

[0142] The length-to-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 400 r / min, the feeding speed of the main feeding system is 50 Hz, and the feeding speed of the side feeding system is 6 Hz.

[0143] Comparative Example 1

[0144] This comparative example provides a PCT resin composition produced without nitrogen protection during the extrusion process, relative to Example 1, wherein the PCT resin composition is prepared by feeding a PCT resin premix and a reinforcing round glass fiber with a mass ratio of 85.7:5 into a main feeding system and a side feeding system of a twin-screw extruder respectively and then being melt-extruded;

[0145] The PCT resin premix is ​​made of 51 parts by weight of PCT resin, 30.2 parts by weight of modified whitening agent, 2 parts by weight of toughening agent ethylene-butyl acrylate-glycidyl methacrylate copolymer (EBA-GMA), 0.5 parts by weight of nucleating agent sodium montanate, 0.5 parts by weight of lubricant ethylene acrylic acid copolymer (EAA), 0.7 parts by weight of light stabilizer methyl amide light stabilizer, 0.2 parts by weight of phosphite antioxidant and 0.4 parts by weight of benzofuranone antioxidant, and 0.2 parts by weight of anti-hydrolysis agent polycarbodiimide;

[0146] The modified brightener is prepared by heating and modifying the brightener silicon-aluminum coated nano titanium dioxide and the silane coupling agent in a mass ratio of 30:0.2;

[0147] The PCT resin composition has a reflectivity of 96.48%, a tensile strength of 45.23 MPa, a flexural strength of 83.67 MPa, and an impact strength of 2.35 kJ / m 2 The hydrolysis aging tensile strength retention rate is 93.60%, the heat deformation temperature is 193.7℃, the color value (L value) before aging is 96.55, the color value (L value) after aging is 90.21, and the color value (L value) difference before and after aging is 5.22.

[0148] The reinforcing agent is round glass fiber with a fiber diameter of ≤10 μm.

[0149] The PCT resin has a melt index of 20 g / 10 min at a temperature of 300° C. and a load of 1.2 kg;

[0150] This comparative example also provides a method for preparing a PCT resin composition, comprising the following steps:

[0151] Step 1, drying poly(cyclohexylene dimethylene terephthalate) resin (PCT resin) for standby use; the first drying temperature is 100° C., the time is 8 hours, and the dried PCT resin is powdered using a high-speed powdering machine;

[0152] The brightener is dried for the second time and then used for later use; the temperature of the second drying is 80°C and the time is 5h;

[0153] The enhancer is dried for the third time and then used for later use; the temperature of the third drying is 80°C and the time is 4h;

[0154] Step 2, putting the coupling agent into the brightener dried in step 1, and stirring at high speed to obtain a modified brightener; the high-speed stirring rate is 500 rad / min, and the time is 8 minutes, so that the coupling agent reacts with the hydroxyl group or oxide included in the brightener to form a corresponding chemical bond, thereby modifying the brightener and improving the dispersibility and stability of the brightener; wherein the modified brightener is placed for no more than 24 hours to prevent it from combining with moisture in the air again and affecting subsequent processes;

[0155] Step 3, the polycyclohexylene dimethylene terephthalate resin powdered in step 1, the modified brightener, toughening agent, nucleating agent, lubricant, light stabilizer, antioxidant, and anti-hydrolysis agent in step 2 are mixed at a high speed according to a proportion at a rate of 1000 rad / min for 3 minutes to obtain a PCT resin premix;

[0156] Step 4, feeding the PCT resin premix of step 3 and the reinforcing agent dried in step 1 into the main feeding system and the side feeding system of the twin-screw extruder respectively and extruding by melt, and finally extruding and granulating by a granulator to obtain a PCT resin composition;

[0157] The main feeding system is in communication with a zone one of the twin-screw extruder, and the side feeding system is in communication with a zone four of the twin-screw extruder;

[0158] The twin-screw extruder includes ten temperature zones, and the temperatures of the zones are set to 260°C for zone 1, 265°C for zone 2, 265°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 270°C for zone 7, 280°C for zone 8, 280°C for zone 9, and 280°C for zone 10;

[0159] The length-to-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 200 r / min, the feeding speed of the main feeding system is 25.5 Hz, and the feeding speed of the side feeding system is 4.5 Hz.

[0160] Comparative Example 2

[0161] This comparative example provides a PCT resin composition prepared without powdering the PCT resin relative to Example 1, wherein the PCT resin composition is prepared by feeding a PCT resin premix and a reinforcing round glass fiber in a mass ratio of 85.7:5 into a main feeding system and a side feeding system of a twin-screw extruder respectively and then being melt-extruded;

[0162] The PCT resin premix is ​​made of 51 parts by weight of PCT resin, 30.2 parts by weight of modified whitening agent, 2 parts by weight of toughening agent ethylene-butyl acrylate-glycidyl methacrylate copolymer (EBA-GMA), 0.5 parts by weight of nucleating agent sodium montanate, 0.5 parts by weight of lubricant ethylene acrylic acid copolymer (EAA), 0.7 parts by weight of light stabilizer methyl amide light stabilizer, 0.2 parts by weight of phosphite antioxidant and 0.4 parts by weight of benzofuranone antioxidant, and 0.2 parts by weight of anti-hydrolysis agent polycarbodiimide;

[0163] The modified brightener is prepared by heating and modifying the brightener silicon-aluminum coated nano titanium dioxide and the silane coupling agent in a mass ratio of 30:0.2;

[0164] The PCT resin composition has a reflectivity of 95.90%, a tensile strength of 42.29 MPa, a flexural strength of 79.36 MPa, and an impact strength of 1.71 kJ / m 2 The hydrolysis aging tensile strength retention rate is 93.26%, the heat deformation temperature is 190.3℃, the color value (L value) before aging is 96.55, the color value (L value) after aging is 90.21, and the color value (L value) difference before and after aging is 6.34.

[0165] The reinforcing agent is round glass fiber with a fiber diameter of ≤10 μm.

[0166] The PCT resin has a melt index of 20 g / 10 min at a temperature of 300° C. and a load of 1.2 kg;

[0167] This comparative example also provides a method for preparing a PCT resin composition, comprising the following steps:

[0168] Step 1, drying poly(cyclohexylene dimethylene terephthalate) resin (PCT resin) for standby use; the first drying temperature is 100° C. and the time is 8 hours;

[0169] The brightener is dried for the second time and then used for later use; the temperature of the second drying is 80°C and the time is 5h;

[0170] The enhancer is dried for the third time and then used for later use; the temperature of the third drying is 80°C and the time is 4h;

[0171] Step 2, putting the coupling agent into the brightener dried in step 1, and stirring at high speed to obtain a modified brightener; the high-speed stirring rate is 500 rad / min, and the time is 8 minutes, so that the coupling agent reacts with the hydroxyl group or oxide included in the brightener to form a corresponding chemical bond, thereby modifying the brightener and improving the dispersibility and stability of the brightener; wherein the modified brightener is placed for no more than 24 hours to prevent it from combining with moisture in the air again and affecting subsequent processes;

[0172] Step 3, the polycyclohexylene dimethylene terephthalate resin of step 1, the modified brightener, toughening agent, nucleating agent, lubricant, light stabilizer, antioxidant, and anti-hydrolysis agent of step 2 are mixed at a high speed according to a proportion at a rate of 1000 rad / min for 3 minutes to obtain a PCT resin premix;

[0173] Step 4, feeding the PCT resin premix of step 3 and the reinforcing agent dried in step 1 into the main feeding system and the side feeding system of the twin-screw extruder respectively and extrude them by melt, and introducing nitrogen into the main feeding system and the side feeding system respectively during the extrusion process, and finally obtaining a PCT resin composition by extrusion and granulation using a granulator;

[0174] The main feeding system is in communication with a zone one of the twin-screw extruder, and the side feeding system is in communication with a zone four of the twin-screw extruder;

[0175] The twin-screw extruder includes ten temperature zones, and the temperatures of the zones are set to 260°C for zone 1, 265°C for zone 2, 265°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 270°C for zone 7, 280°C for zone 8, 280°C for zone 9, and 280°C for zone 10;

[0176] The length-to-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 200 r / min, the feeding speed of the main feeding system is 25.5 Hz, and the feeding speed of the side feeding system is 4.5 Hz.

[0177] Comparative Example 3

[0178] This comparative example provides a PCT resin composition prepared by feeding a PCT resin premix and a reinforcing agent from a main feeding system into a twin-screw extruder relative to Example 1, that is, the PCT resin composition is prepared by feeding a PCT resin premix and a reinforcing agent round glass fiber with a mass ratio of 85.7:5 into the main feeding system of a twin-screw extruder through melt extrusion;

[0179] The PCT resin premix is ​​made of 51 parts by weight of PCT resin, 30.2 parts by weight of modified whitening agent, 2 parts by weight of toughening agent ethylene-butyl acrylate-glycidyl methacrylate copolymer (EBA-GMA), 0.5 parts by weight of nucleating agent sodium montanate, 0.5 parts by weight of lubricant ethylene acrylic acid copolymer (EAA), 0.7 parts by weight of light stabilizer methyl amide light stabilizer, 0.2 parts by weight of phosphite antioxidant and 0.4 parts by weight of benzofuranone antioxidant, and 0.2 parts by weight of anti-hydrolysis agent polycarbodiimide;

[0180] The modified brightener is prepared by heating and modifying the brightener silicon-aluminum coated nano titanium dioxide and the silane coupling agent in a mass ratio of 30:0.2;

[0181] The PCT resin composition has a reflectivity of 95.85%, a tensile strength of 40.68 MPa, a flexural strength of 76.45 MPa, and an impact strength of 1.20 kJ / m 2 The hydrolysis aging tensile strength retention rate is 89.26%, the heat deformation temperature is 190.4℃, the color value (L value) before aging is 96.31, the color value (L value) after aging is 90.43, and the color value (L value) difference before and after aging is 5.88.

[0182] The reinforcing agent is round glass fiber with a fiber diameter of ≤10 μm.

[0183] The PCT resin has a melt index of 20 g / 10 min at a temperature of 300° C. and a load of 1.2 kg;

[0184] This comparative example also provides a method for preparing a PCT resin composition, comprising the following steps:

[0185] Step 1, drying poly(cyclohexylene dimethylene terephthalate) resin (PCT resin) for standby use; the first drying temperature is 100° C., the time is 8 hours, and the dried PCT resin is powdered using a high-speed powdering machine;

[0186] The brightener is dried for the second time and then used for later use; the temperature of the second drying is 80°C and the time is 5h;

[0187] The enhancer is dried for the third time and then used for later use; the temperature of the third drying is 80°C and the time is 4h;

[0188] Step 2, putting the coupling agent into the brightener dried in step 1, and stirring at high speed to obtain a modified brightener; the high-speed stirring rate is 500 rad / min, and the time is 8 minutes, so that the coupling agent reacts with the hydroxyl group or oxide included in the brightener to form a corresponding chemical bond, thereby modifying the brightener and improving the dispersibility and stability of the brightener; wherein the modified brightener is placed for no more than 24 hours to prevent it from combining with moisture in the air again and affecting subsequent processes;

[0189] Step 3, the polycyclohexylene dimethylene terephthalate resin powdered in step 1, the modified brightener, toughening agent, nucleating agent, lubricant, light stabilizer, antioxidant, and anti-hydrolysis agent in step 2 are mixed at a high speed according to a proportion at a rate of 1000 rad / min for 3 minutes to obtain a PCT resin premix;

[0190] Step 4, feeding the PCT resin premix of step 3 and the reinforcing agent dried in step 1 into the main feeding system of the twin-screw extruder for melt extrusion, and introducing nitrogen into the main feeding system during the extrusion process, and finally using a granulator for extrusion and granulation to obtain a PCT resin composition;

[0191] The main feeding system is in communication with a zone of the twin-screw extruder;

[0192] The twin-screw extruder includes ten temperature zones, and the temperatures of the zones are set to 260°C for zone 1, 265°C for zone 2, 265°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 270°C for zone 7, 280°C for zone 8, 280°C for zone 9, and 280°C for zone 10;

[0193] The length-to-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 200 r / min, and the feeding speed of the main feeding system is 25.5 Hz.

[0194] Comparative Example 4

[0195] This comparative example provides a PCT resin composition prepared by using a reinforcing round glass fiber thicker than that of Example 1 and without adding an anti-hydrolysis agent, wherein the PCT resin composition is prepared by feeding a PCT resin premix and a reinforcing round glass fiber with a mass ratio of 85.5:5 into a main feeding system and a side feeding system of a twin-screw extruder respectively and then extruding the PCT resin premix and the reinforcing round glass fiber through melt extrusion;

[0196] The PCT resin premix is ​​made of 51 parts by weight of PCT resin, 30.2 parts by weight of modified whitening agent, 2 parts by weight of toughening agent ethylene-butyl acrylate-glycidyl methacrylate copolymer (EBA-GMA), 0.5 parts by weight of nucleating agent sodium salt of montanic acid, 0.5 parts by weight of lubricant ethylene acrylic acid copolymer (EAA), 0.7 parts by weight of light stabilizer methylamide light stabilizer, 0.2 parts by weight of phosphite antioxidant and 0.4 parts by weight of benzofuranone antioxidant;

[0197] The modified brightener is prepared by heating and modifying the brightener silicon-aluminum coated nano titanium dioxide and the silane coupling agent in a mass ratio of 30:0.2;

[0198] The PCT resin composition has a reflectivity of 97.52%, a tensile strength of 47.36 MPa, a flexural strength of 86.34 MPa, and an impact strength of 3.25 kJ / m 2 The hydrolysis aging tensile strength retention rate is 91.45%, the heat deformation temperature is 191.9℃, the color value (L value) before aging is 97.22, the color value (L value) after aging is 92.34, and the color value (L value) difference before and after aging is 4.88.

[0199] The reinforcing agent is round glass fiber with a fiber diameter ranging from 13 to 16 μm.

[0200] The PCT resin has a melt index of 20 g / 10 min at a temperature of 300° C. and a load of 1.2 kg;

[0201] This comparative example also provides a method for preparing a PCT resin composition, comprising the following steps:

[0202] Step 1, drying poly(cyclohexylene dimethylene terephthalate) resin (PCT resin) for standby use; the first drying temperature is 100° C., the time is 8 hours, and the dried PCT resin is powdered using a high-speed powdering machine;

[0203] The brightener is dried for the second time and then used for later use; the temperature of the second drying is 80°C and the time is 5h;

[0204] The enhancer is dried for the third time and then used for later use; the temperature of the third drying is 80°C and the time is 4h;

[0205] Step 2, putting the coupling agent into the brightener dried in step 1, and stirring at high speed to obtain a modified brightener; the high-speed stirring rate is 500 rad / min, and the time is 8 minutes, so that the coupling agent reacts with the hydroxyl group or oxide included in the brightener to form a corresponding chemical bond, thereby modifying the brightener and improving the dispersibility and stability of the brightener; wherein the modified brightener is placed for no more than 24 hours to prevent it from combining with moisture in the air again and affecting subsequent processes;

[0206] Step 3, the polycyclohexylene dimethylene terephthalate resin powdered in step 1, the modified brightener, toughening agent, nucleating agent, lubricant, light stabilizer, and antioxidant in step 2 are mixed at a high speed according to a proportion at a rate of 1000 rad / min for 3 minutes to obtain a PCT resin premix;

[0207] Step 4, feeding the PCT resin premix of step 3 and the reinforcing agent dried in step 1 into the main feeding system and the side feeding system of the twin-screw extruder respectively and extrude them by melt, and introducing nitrogen into the main feeding system and the side feeding system respectively during the extrusion process, and finally obtaining a PCT resin composition by extrusion and granulation using a granulator;

[0208] The main feeding system is in communication with a zone one of the twin-screw extruder, and the side feeding system is in communication with a zone four of the twin-screw extruder;

[0209] The twin-screw extruder includes ten temperature zones, and the temperatures of the zones are set to 260°C for zone 1, 265°C for zone 2, 265°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 270°C for zone 7, 280°C for zone 8, 280°C for zone 9, and 280°C for zone 10;

[0210] The length-to-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 200 r / min, the feeding speed of the main feeding system is 25.5 Hz, and the feeding speed of the side feeding system is 4.5 Hz.

[0211] Comparative Example 5

[0212] This comparative example provides a PCT resin composition prepared by using only a single antioxidant relative to Example 1, wherein the PCT resin composition is prepared by feeding a PCT resin premix and a reinforcing agent round glass fiber in a mass ratio of 85.7:5 into a main feeding system and a side feeding system of a twin-screw extruder respectively and then being melt-extruded;

[0213] The PCT resin premix is ​​made of 51 parts by weight of PCT resin, 30.2 parts by weight of modified whitening agent, 2 parts by weight of toughening agent ethylene-butyl acrylate-glycidyl methacrylate copolymer (EBA-GMA), 0.5 parts by weight of nucleating agent sodium montanate, 0.5 parts by weight of lubricant ethylene acrylic acid copolymer (EAA), 0.7 parts by weight of light stabilizer methyl amide light stabilizer, 0.6 parts by weight of phosphite antioxidant, and 0.2 parts by weight of anti-hydrolysis agent polycarbodiimide;

[0214] The modified brightener is prepared by heating and modifying the brightener silicon-aluminum coated nano titanium dioxide and the silane coupling agent in a mass ratio of 30:0.2;

[0215] The PCT resin composition has a reflectivity of 97.32%, a tensile strength of 48.37 MPa, a flexural strength of 88.04 MPa, and an impact strength of 3.48 kJ / m 2 The hydrolysis aging tensile strength retention rate is 94.87%, the heat deformation temperature is 190.4℃, the color value (L value) before aging is 96.89, the color value (L value) after aging is 91.02, and the color value (L value) difference before and after aging is 5.87.

[0216] The reinforcing agent is round glass fiber with a fiber diameter of ≤10 μm.

[0217] The PCT resin has a melt index of 20 g / 10 min at a temperature of 300° C. and a load of 1.2 kg;

[0218] This comparative example also provides a method for preparing a PCT resin composition, comprising the following steps:

[0219] Step 1, drying poly(cyclohexylene dimethylene terephthalate) resin (PCT resin) for standby use; the first drying temperature is 100° C., the time is 8 hours, and the dried PCT resin is powdered using a high-speed powdering machine;

[0220] The brightener is dried for the second time and then used for later use; the temperature of the second drying is 80°C and the time is 5h;

[0221] The enhancer is dried for the third time and then used for later use; the temperature of the third drying is 80°C and the time is 4h;

[0222] Step 2, putting the coupling agent into the brightener dried in step 1, and stirring at high speed to obtain a modified brightener; the high-speed stirring rate is 500 rad / min, and the time is 8 minutes, so that the coupling agent reacts with the hydroxyl group or oxide included in the brightener to form a corresponding chemical bond, thereby modifying the brightener and improving the dispersibility and stability of the brightener; wherein the modified brightener is placed for no more than 24 hours to prevent it from combining with moisture in the air again and affecting subsequent processes;

[0223] Step 3, the polycyclohexylene dimethylene terephthalate resin powdered in step 1, the modified brightener, toughening agent, nucleating agent, lubricant, light stabilizer, antioxidant, and anti-hydrolysis agent in step 2 are mixed at a high speed according to a proportion at a rate of 1000 rad / min for 3 minutes to obtain a PCT resin premix;

[0224] Step 4, feeding the PCT resin premix of step 3 and the reinforcing agent dried in step 1 into the main feeding system and the side feeding system of the twin-screw extruder respectively and extrude them by melt, and introducing nitrogen into the main feeding system and the side feeding system respectively during the extrusion process, and finally obtaining a PCT resin composition by extrusion and granulation using a granulator;

[0225] The main feeding system is in communication with a zone one of the twin-screw extruder, and the side feeding system is in communication with a zone four of the twin-screw extruder;

[0226] The twin-screw extruder includes ten temperature zones, and the temperatures of the zones are set to 260°C for zone 1, 265°C for zone 2, 265°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 270°C for zone 7, 280°C for zone 8, 280°C for zone 9, and 280°C for zone 10;

[0227] The length-to-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 200 r / min, the feeding speed of the main feeding system is 25.5 Hz, and the feeding speed of the side feeding system is 4.5 Hz.

[0228] The performance of the PCT resin composition in Examples 1-4 and Comparative Examples 1-5 was compared, and the comparison results are shown in Table 1:

[0229] Table 1 Comparison of the properties of the PCT resin compositions in Examples 1-4 and Comparative Examples 1-5

[0230]

[0231] By comparing the PCT resin compositions prepared in Examples 1-5 with those prepared in Example 1, changing any component or ratio in the prepared formula, or changing any condition of the preparation process, will cause the PCT resin composition to lose the performance obtained by the corresponding component or process, and will also cause the overall performance to decline. It can be seen that the present invention can obtain a PCT resin composition with relatively stable and high quality performance through specific preparation raw materials, ratios and processes. The PCT resin composition prepared by the specific formula, ratio and process of the present invention can also meet the use requirements of high-quality products in the field of LED packaging, such as the requirements of a reflectivity of more than 95% or a tensile strength retention rate of more than 90% after hydrolysis aging.

[0232] It should be understood that the present invention is not limited to what has been described above and that various modifications and changes may be made without departing from its scope. The scope of the present invention is limited only by the appended claims.

Claims

1. A PCT resin composition, characterized in that The PCT resin composition is prepared by feeding a PCT resin premix and a reinforcing agent round glass fiber in a mass ratio of 85.7:5 into a main feeding system and a side feeding system of a twin-screw extruder respectively and then being melt-extruded; The PCT resin premix is ​​made of 51 parts by weight of PCT resin, 30.2 parts by weight of modified whitening agent, 2 parts by weight of toughening agent ethylene-butyl acrylate-glycidyl methacrylate copolymer, 0.5 parts by weight of nucleating agent sodium salt of montanic acid, 0.5 parts by weight of lubricant ethylene acrylic acid copolymer, 0.7 parts by weight of light stabilizer methyl amide light stabilizer, 0.2 parts by weight of phosphite antioxidant and 0.4 parts by weight of benzofuranone antioxidant, and 0.2 parts by weight of anti-hydrolysis agent polycarbodiimide; The modified brightener is used in a mass ratio of 30: It is prepared by heating and modifying 0.2 whitening agent silicon-aluminum coated nano titanium dioxide and silane coupling agent; The PCT resin composition has a reflectivity of 98.87%, a tensile strength of 49.25 MPa, a flexural strength of 89.42 MPa, and an impact strength of 3.65 kJ / m 2 , the hydrolysis aging tensile strength retention rate is 95.52%, the heat deformation temperature is 195.6℃, the L value before aging is 98.33, the L value after aging is 94.13, and the difference between the L values ​​before and after aging is 4.20; The reinforcing agent is round glass fiber with a fiber diameter of ≤10 μm; The PCT resin has a melt index of 20 g / 10 min at a temperature of 300° C. and a load of 1.2 kg; The preparation method of the PCT resin composition comprises the following steps: Step 1, drying the poly(cyclohexylene dimethylene terephthalate) resin for standby use; the first drying temperature is 100° C., the time is 8 hours, and the dried PCT resin is powdered using a high-speed powdering machine; The brightener is dried for the second time and then used for later use; the temperature of the second drying is 80°C and the time is 5h; The enhancer is dried for the third time and then used for later use; the temperature of the third drying is 80°C and the time is 4h; Step 2, adding the coupling agent into the brightener dried in step 1, and stirring at high speed to obtain a modified brightener; the high-speed stirring rate is 500 rad / min, and the time is 8 minutes; Step 3, the polycyclohexylene dimethylene terephthalate resin powdered in step 1, the modified brightener, toughening agent, nucleating agent, lubricant, light stabilizer, antioxidant, and anti-hydrolysis agent in step 2 are mixed at a high speed according to a proportion at a rate of 1000 rad / min for 3 minutes to obtain a PCT resin premix; Step 4, feeding the PCT resin premix of step 3 and the reinforcing agent dried in step 1 into the main feeding system and the side feeding system of the twin-screw extruder respectively and extrude them by melt, and introducing nitrogen into the main feeding system and the side feeding system respectively during the extrusion process, and finally obtaining a PCT resin composition by extrusion and granulation using a granulator; The main feeding system is in communication with a zone one of the twin-screw extruder, and the side feeding system is in communication with a zone four of the twin-screw extruder; The twin-screw extruder includes ten temperature zones, and the temperatures of the zones are set to 260°C for zone 1, 265°C for zone 2, 265°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 270°C for zone 7, 280°C for zone 8, 280°C for zone 9, and 280°C for zone 10; The length-to-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 200 r / min, the feeding speed of the main feeding system is 25.5 Hz, and the feeding speed of the side feeding system is 4.5 Hz.

2. A PCT resin composition, characterized in that: The PCT resin composition is prepared by feeding a PCT resin premix and a reinforcing round glass fiber in a mass ratio of 85.1:17 into a main feeding system and a side feeding system of a twin-screw extruder respectively and then being melt-extruded; The PCT resin premix is ​​made of 50.7 parts by weight of PCT resin, 28.3 parts by weight of modified brightener, 2 parts by weight of toughening agent polyolefin elastomer, 0.2 parts by weight of nucleating agent N-butylpyracloic acid methyl salt, 2 parts by weight of lubricant silicone masterbatch, 0.5 parts by weight of light stabilizer methylamide light stabilizer, 0.2 parts by weight of phosphite antioxidant, 0.4 parts by weight of benzofuranone antioxidant, 0.4 parts by weight of acrylate antioxidant, and 0.4 parts by weight of anti-hydrolysis agent polycarbodiimide; The modified brightener is used in a mass ratio of 28: It is prepared by heating and modifying 0.3 whitening agent silicon-aluminum coated nano titanium dioxide and titanate coupling agent; The PCT resin composition has a reflectivity of 98.42%, a tensile strength of 48.54 MPa, a flexural strength of 90.01 MPa, and an impact strength of 3.34 kJ / m 2 , the hydrolysis aging tensile strength retention rate is 94.80%, the heat deformation temperature is 194.4℃, the L value before aging is 97.57, the L value after aging is 93.45, and the difference between the L values ​​before and after aging is 4.12; The reinforcing agent is round glass fiber with a fiber diameter of ≤10 μm; The PCT resin has a melt index of 30 g / 10 min at a temperature of 300° C. and a load of 1.2 kg; The preparation method of the PCT resin composition comprises the following steps: Step 1, drying the poly(cyclohexylene dimethylene terephthalate) resin for standby use; the first drying temperature is 110° C., the time is 5 hours, and the dried PCT resin is powdered using a high-speed powder grinder; The brightener is dried for the second time and then used for later use; the temperature of the second drying is 90°C and the time is 4h; The enhancer is dried for the third time and then used for later use; the temperature of the third drying is 90°C and the time is 3h; Step 2, adding the coupling agent into the brightener dried in step 1, and stirring at high speed to obtain a modified brightener; the high-speed stirring rate is 1000 rad / min, and the time is 5 min; Step 3, the polycyclohexylene dimethylene terephthalate resin powdered in step 1, the modified brightener, toughening agent, nucleating agent, lubricant, light stabilizer, antioxidant, and anti-hydrolysis agent in step 2 are mixed at a high speed according to a proportion at a rate of 500 rad / min for 5 minutes to obtain a PCT resin premix; Step 4, feeding the PCT resin premix of step 3 and the reinforcing agent dried in step 1 into the main feeding system and the side feeding system of the twin-screw extruder respectively and extrude them by melt, and introducing nitrogen into the main feeding system and the side feeding system respectively during the extrusion process, and finally obtaining a PCT resin composition by extrusion and granulation using a granulator; The main feeding system is in communication with a zone one of the twin-screw extruder, and the side feeding system is in communication with a zone four of the twin-screw extruder; The twin-screw extruder includes ten temperature zones, and the temperatures of the zones are respectively set at 280°C for zone 1, 260°C for zone 2, 260°C for zone 3, 280°C for zone 4, 240°C for zone 5, 240°C for zone 6, 260°C for zone 7, 260°C for zone 8, 280°C for zone 9, and 280°C for zone 10; The length-to-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 300 r / min, the feeding speed of the main feeding system is 10 Hz, and the feeding speed of the side feeding system is 7 Hz.

3. A PCT resin composition, characterized in that The PCT resin composition is prepared by feeding a PCT resin premix and a reinforcing round glass fiber in a mass ratio of 60.5:20 into a main feeding system and a side feeding system of a twin-screw extruder respectively and then being melt-extruded; The PCT resin premix is ​​composed of 45 parts by weight of PCT resin, 10.8 parts by weight of modified whitening agent, 1 part by weight of toughening agent methyl methacrylate-butadiene-styrene copolymer, 0.1 parts by weight of a nucleating agent, sodium montanate, 1 part by weight of a lubricating agent, oxidized polyethylene wax, 2 parts by weight of a light stabilizer, methyl amide type light stabilizer, 0.3 parts by weight of a benzofuranone type antioxidant, 0.2 parts by weight of an acrylate type antioxidant, and 0.1 parts by weight of an anti-hydrolysis agent, polycarbodiimide; The modified brightener is used in a mass ratio of 10: It is prepared by heating and modifying 0.8 whitening agent silicon-aluminum coated nano titanium dioxide and aluminate coupling agent; The PCT resin composition has a reflectivity of 98.53%, a tensile strength of 49.12 MPa, a flexural strength of 89.44 MPa, and an impact strength of 3.05 kJ / m 2 , the hydrolysis aging tensile strength retention rate is 95.09%, the heat deformation temperature is 194.1℃, the L value before aging is 98.42, the L value after aging is 93.48, and the difference between the L values ​​before and after aging is 4.94; The reinforcing agent is round glass fiber with a fiber diameter of ≤10 μm; The PCT resin has a melt index of 40 g / 10 min at a temperature of 300° C. and a load of 1.2 kg; The preparation method of the PCT resin composition comprises the following steps: Step 1, drying the poly(cyclohexylene dimethylene terephthalate) resin for standby use; the first drying temperature is 110° C., the time is 5 hours, and the dried PCT resin is powdered using a high-speed powder grinder; The brightener is dried for the second time and then used for later use; the temperature of the second drying is 90°C and the time is 5h; The enhancer is dried for the third time and then used for later use; the temperature of the third drying is 80°C and the time is 3h; Step 2, adding the coupling agent into the brightener dried in step 1, and stirring at high speed to obtain a modified brightener; the high-speed stirring rate is 800 rad / min, and the time is 6 minutes; Step 3, the polycyclohexylene dimethylene terephthalate resin powdered in step 1, the modified brightener, toughening agent, nucleating agent, lubricant, light stabilizer, antioxidant, and anti-hydrolysis agent in step 2 are mixed at a high speed according to a proportion at a rate of 700 rad / min for 4 minutes to obtain a PCT resin premix; Step 4, feeding the PCT resin premix of step 3 and the reinforcing agent dried in step 1 into the main feeding system and the side feeding system of the twin-screw extruder respectively and extrude them by melt, and introducing nitrogen into the main feeding system and the side feeding system respectively during the extrusion process, and finally obtaining a PCT resin composition by extrusion and granulation using a granulator; The main feeding system is in communication with a zone one of the twin-screw extruder, and the side feeding system is in communication with a zone four of the twin-screw extruder; The twin-screw extruder includes ten temperature zones, and the temperatures of the zones are set to 260°C for zone 1, 280°C for zone 2, 280°C for zone 3, 240°C for zone 4, 240°C for zone 5, 240°C for zone 6, 280°C for zone 7, 260°C for zone 8, 260°C for zone 9, and 260°C for zone 10; The length-to-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 400 r / min, the feeding speed of the main feeding system is 40 Hz, and the feeding speed of the side feeding system is 5.5 Hz.

4. A PCT resin composition, characterized in that The PCT resin composition is prepared by feeding a PCT resin premix and a reinforcing agent round glass fiber in a mass ratio of 123:10 into a main feeding system and a side feeding system of a twin-screw extruder respectively and then being melt-extruded; The PCT resin premix is ​​made of 60 parts by weight of PCT resin, 41 parts by weight of modified brightener, 8 parts by weight of toughening agent methyl methacrylate-butadiene-styrene copolymer, 2 parts by weight of nucleating agent N-butylpyracloic acid methyl salt, 3 parts by weight of lubricant oxidized polyethylene wax, 3 parts by weight of light stabilizer methyl amide light stabilizer, 1 part by weight of benzofuranone antioxidant and 2 parts by weight of acrylate antioxidant, and 3 parts by weight of anti-hydrolysis agent polycarbodiimide; The modified brightener is prepared by heating and modifying the brightener silicon-aluminum coated nano titanium dioxide and aluminum zirconate coupling agent in a mass ratio of 40:1; The PCT resin composition has a reflectivity of 98.61%, a tensile strength of 48.97 MPa, a flexural strength of 89.65 MPa, and an impact strength of 3.34 kJ / m 2 , the hydrolysis aging tensile strength retention rate is 95.28%, the heat deformation temperature is 193.4℃, the L value before aging is 97.92, the L value after aging is 94.10, and the difference between the L values ​​before and after aging is 3.82; The reinforcing agent is round glass fiber with a fiber diameter of ≤10 μm; The PCT resin has a melt index of 50 g / 10 min at a temperature of 300° C. and a load of 1.2 kg; The preparation method of the PCT resin composition comprises the following steps: Step 1, drying the poly(cyclohexylene dimethylene terephthalate) resin for standby use; the first drying temperature is 100° C., the time is 7 hours, and the dried PCT resin is powdered using a high-speed powdering machine; The brightener is dried for the second time and then used for later use; the temperature of the second drying is 90°C and the time is 4h; The enhancer is dried for the third time and then used for later use; the temperature of the third drying is 80°C and the time is 4h; Step 2, adding the coupling agent into the brightener dried in step 1, and stirring at high speed to obtain a modified brightener; the high-speed stirring rate is 800 rad / min, and the time is 7 min; Step 3, the polycyclohexylene dimethylene terephthalate resin powdered in step 1, the modified brightener, toughening agent, nucleating agent, lubricant, light stabilizer, antioxidant, and anti-hydrolysis agent in step 2 are mixed at a high speed according to a proportion at a rate of 800 rad / min for 4 minutes to obtain a PCT resin premix; Step 4, feeding the PCT resin premix of step 3 and the reinforcing agent dried in step 1 into the main feeding system and the side feeding system of the twin-screw extruder respectively and extrude them by melt, and introducing nitrogen into the main feeding system and the side feeding system respectively during the extrusion process, and finally obtaining a PCT resin composition by extrusion and granulation using a granulator; The main feeding system is in communication with a zone one of the twin-screw extruder, and the side feeding system is in communication with a zone four of the twin-screw extruder; The twin-screw extruder includes ten temperature zones, and the temperatures of the zones are set to 260°C for zone 1, 280°C for zone 2, 280°C for zone 3, 240°C for zone 4, 280°C for zone 5, 280°C for zone 6, 280°C for zone 7, 260°C for zone 8, 260°C for zone 9, and 270°C for zone 10; The length-to-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 400 r / min, the feeding speed of the main feeding system is 50 Hz, and the feeding speed of the side feeding system is 6 Hz.

Citation Information

Patent Citations

  • Polyester composition as well as preparation method and application thereof

    CN118530563A

  • Glass fiber reinforced PCT resin and preparation method thereof

    CN103589121A

  • Polyester composition and preparation method thereof

    CN106987101A